Protein Concentrates on Tepary Bean (Phaseolus acutifolius Gray) as a Functional Ingredient: In silico Docking of Tepary Bean Lectin to Peroxisome Proliferator-Activated Receptor Gamma - López-Ibarra, Cristina; Ruiz-López, Felipe de Jesús; Bautista-Villarreal, Minerva; Báez-González, Juan Gabriel; Rodríguez Romero, Beatriz Adriana; González-Martínez, Blanca Edelia; López-Cabanillas Lomelí, Manuel; Vázquez-Rodríguez, Jesús Alberto (Frontiers in Nutrition, 2021)
The tepary bean (Phaseolus acutifolius Gray) is the US – Mexico frontier native crop, produces high yields in agriculture, and needs to be reconsidered by nutritional and functional properties itself. This study aimed to determine the technological and nutritional properties of flours and protein concentrates of tepary bean, besides determining an in silico agonist effect of tepary bean lectin to Peroxisome proliferator-activated receptor gamma (PPAR-γ). We evaluated the technological properties of raw samples (tepary flour & tepary protein concentrate) and cooked samples (tepary flour and tepary protein concentrate). The flours present a significant difference (p<0.05) concerning protein concentrates in water absorption and oil absorption capacity. The raw samples' emulsifying capacity was higher than that reported in the literature for other legumes, but not the cooked samples. The samples' foaming capacity had no significant difference treatments (p> 0.05), and cooked tepary bean protein concentrate presented complete gelation at a lower concentration (2%). Nutritionally, raw samples present protein percentage of 23.46±0.06, 71.38±0.44 and cooked samples 25.27±0.04, 62.69±0.14; chemical score of 72, 86, 82, 72; in vitro protein digestibility (%) = 48.20±0.31, 49.80±0.80, 61.77±1.70, 63.61±4.19 and a C-PER = 0.86, 1.34, 1.93, 1.81; respectively. All the samples showed Methionine+Cysteine as the limit amino acid. All these nutritional data are very similar to the common bean (Phaseolus vulgaris). SDS-PAGE preserves the lectin fraction in both protein concentrates. The in silico study of tepary lectin (PDB: 6tt9) show that the peptides that presented values below -120 Kcal/mol were 7 = PEW, VSVGF, PSQK, TTPW, ATSF, ITY, TSF; being VSVGF, PSQK & PEW with the highest affinity for active sites of the PAPRγ receptor (binding energies from -5.32 to -7.04 Kcal/mol). These peptides could show antiadipogenic or antidiabetic activity based on the intermolecular bond energies and open an interesting research item.